2021
DOI: 10.3390/ijms22147578
|View full text |Cite
|
Sign up to set email alerts
|

Haplotype Analysis of BADH1 by Next-Generation Sequencing Reveals Association with Salt Tolerance in Rice during Domestication

Abstract: Betaine aldehyde dehydrogenase 1 (BADH1), a paralog of the fragrance gene BADH2, is known to be associated with salt stress through the accumulation of synthesized glycine betaine (GB), which is involved in the response to abiotic stresses. Despite the unclear association between BADH1 and salt stress, we observed the responses of eight phenotypic characteristics (germination percentage (GP), germination energy (GE), germination index (GI), mean germination time (MGT), germination rate (GR), shoot length (SL),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…Next generation gene sequencing opens the avenue to revealing salt tolerance mechanisms more precisely. Min et al [20] reported that haplotype analysis of BADH1 by next-generation sequencing reveals an association with salt tolerance in rice during domestication. Despite the unclear association between BADH1 and salt stress, these findings can be useful for future research development related to its gene expression [20].…”
mentioning
confidence: 99%
“…Next generation gene sequencing opens the avenue to revealing salt tolerance mechanisms more precisely. Min et al [20] reported that haplotype analysis of BADH1 by next-generation sequencing reveals an association with salt tolerance in rice during domestication. Despite the unclear association between BADH1 and salt stress, these findings can be useful for future research development related to its gene expression [20].…”
mentioning
confidence: 99%
“…Previous research has highlighted a narrower genetic diversity in japonica compared to indica rice, likely due to a domestication bottleneck [22,53]. Furthermore, breeding efforts over the past century have further narrowed the genetic diversity among cultivars, particularly those selected for cultivation in diverse agro-ecological environments [53,54]. In terms of Tajima's D measurement, indica was the only group with a positive value, suggesting that rare alleles are more likely to be lost during bottleneck events [55].…”
Section: Discussionmentioning
confidence: 99%
“…A transcript level analysis revealed the constitutive expression of BADH2 under normal and stress conditions and the upregulation in BADH1 expression by salt and drought stresses [12] , [50] , [51] . Various studies have revealed the involvement of BADH1 in salt stress tolerance [52] , [53] , [54] , [55] . Furthermore, BADH1 has a much lower affinity for GABAld and higher affinities for other aldehyde substrates than those of BADH2 [12] , [53] , [56] , [57] .…”
Section: Discussionmentioning
confidence: 99%